Identification of nucleobase chemical modifications that reduce the hepatotoxicity of gapmer antisense oligonucleotides. Issue 13 (8th July 2022) - Yoshida, Tokuyuki; Morihiro, Kunihiko; Naito, Yuki; Mikami, Atsushi; Kasahara, Yuuya; Inoue, Takao; Obika, Satoshi
Abstract: Currently, gapmer antisense oligonucleotide (ASO) therapeutics are under clinical development for the treatment of various diseases, including previously intractable human disorders; however, they have the potential to induce hepatotoxicity. Although several groups have reported the reduced hepatotoxicity of gapmer ASOs following chemical modifications of sugar residues or internucleotide linkages, only few studies have described nucleobase modifications to reduce hepatotoxicity. In this study, we introduced single or multiple combinations of 17 nucleobase derivatives, including four novel derivatives, into hepatotoxic locked nucleic acid gapmer ASOs and examined their effects on hepatotoxicity. The results demonstrated successful identification of chemical modifications that strongly reduced the hepatotoxicity of gapmer ASOs. This approach expands the ability to design gapmer ASOs with optimal therapeutic profiles.